Molecular Approaches to Soil, Rhizosphere and Plant Microorganism Analysis - Cooper, J.E (CABI, 2014)
Without the cycling of elements, continuation of life on earth would be impossible, since essential nutrients would rapidly be taken up by organisms and locked in a form that cannot be used by others. The reactions involved in elemental cycling are often chemical in nature, but biochemical reactions also play an important role. Microbes are of prime significance in this process. Microbial and biochemical characteristics are used as potential indicators of soil quality because of their central role in cycling of carbon and nitrogen and their sensitivity to change